2019
DOI: 10.1159/000500926
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the Pretreatment Neutrophil/Lymphocyte Ratio in Patients with Glioblastoma Multiforme Brain Tumors: A Retrospective Cohort Study of Patients Treated with Combined Modality Surgery, Radiation Therapy, and Temozolomide Chemotherapy

Abstract: <b><i>Background:</i></b> Recent studies have shown that the peripheral blood pretreatment neutrophil/lymphocyte ratio (NLR) is a prognostic measure in various cancers. The few studies evaluating NLR in glioblastoma multiforme (GBM) patients yielded inconsistent results. <b><i>Objectives:</i></b> The primary objective of our study was to test the ability of pretreatment NLR to predict the overall survival (OS) and progression-free survival (PFS) of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…One study by Kaya et al used 5 as the cut-off value and found that the NLR was correlated with survival (33), whereas another study by Mason et al used 7.5 as the cut-off value and found that the NLR was not correlated with survival (11), although they used postoperative samples. Notably, a recent study by Brenner et al (35) come to the result that the pretreatment NLR did not have the prognostic value in glioblastoma patients treated with combined modality surgery, radiation, and temozolomide, indicating the prognostic significance of the NLR in some designate cohort remains unclear. The NLR was also found to positively correlate with the expression of Ki-67 (34) and the glioma grade (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study by Kaya et al used 5 as the cut-off value and found that the NLR was correlated with survival (33), whereas another study by Mason et al used 7.5 as the cut-off value and found that the NLR was not correlated with survival (11), although they used postoperative samples. Notably, a recent study by Brenner et al (35) come to the result that the pretreatment NLR did not have the prognostic value in glioblastoma patients treated with combined modality surgery, radiation, and temozolomide, indicating the prognostic significance of the NLR in some designate cohort remains unclear. The NLR was also found to positively correlate with the expression of Ki-67 (34) and the glioma grade (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, one study (14) treated the lymphocyte count as a dichotomous variable, which was different from the remaining studies, and was therefore excluded in the last quantitative synthesis. Finally, there were 2 (11,12), 3 (11, 14, 28), 2 (16,29), 8 (11,(30)(31)(32)(33)(34)(35)(36), and 3 (30,31,37) included studies examining the neutrophil, lymphocyte, and platelet counts and the NLR and PLR, respectively. All the incorporated studies focused on glioblastoma patients performing the multivariate analysis.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant to this statement, empirically, remarkably fully 13 independent studies just between 2018 and 2020 reported the same findings-that a higher neutrophil to lymphocyte ratio-a relative or absolute neutrophilia-correlated with shorter survival in GB [66][67][68][69][70][71][72][73][74][75][76][77][78]. Few parameters in any cancer have been so oft confirmed.…”
Section: Dapsone Gb and Neutrophilsmentioning
confidence: 85%
“…However, no consensus has been reached (21)(22)(23). The prognostic value of SIRI as a new indicator was first found in patients with pancreatic cancer (24).…”
Section: Discussionmentioning
confidence: 99%